Culture of an Antarctic seaweed, Phyllophora antarctica (Phyllophoraceae,Rhodophyceae) - Ohno, Masao (1984)
P(論文) An Antarctic seaweed, Phyllophora antarctica was collected beneath the sea ice of the coast of East Ongul Island (69°00′S, 39°35′E) of Lutzow-Holm Bay. The specimens were carried to the laboratory in Japan by the icebreaker FUJI, and then they were kept at controlled temperature in an incubator for two years. The new fronds appeared from the margin of older thalli at temperature of 3℃ and light intensity of about 3000lx. These plants were maintained under several culture conditions for a long time, but the reproductive organ did not appear on the fronds. The optimum temperature for the growth of the fronds was about 3℃. The growth rate was 20.3±6.9% increase of wet weight per week under the optimum culture condition. The optimum temperature for photoshynthetic activity was between 10℃ and 15℃ under light intensity of 10000lx. departmental bulletin paper